A companion to Renaissance and Baroque art - Bohn, Babette, 1950-; Saslow, James M. (Hoboken : Wiley-Blackwell, 2013)
"Through the masterpieces produced by artists ranging from Michelangelo and Leonardo to Rembrandt, Rubens, and Vermeer, Europe's Renaissance and Baroque period grew into one of the most creative times in world history. A Companion to Renaissance and Baroque Art presents a comprehensive collection of interdisciplinary essays that address major aspects of European visual arts produced from approximately 1300 to 1700, a period of artistic flourishing that many consider the beginning of modern history. These essays, however, transcend the traditional period labels of "Renaissance" and "Baroque" by addressing works from Duccio and Chaucer to Velazquez and Newton as a single continuum, inclusive in terms of both disciplinary and geographical boundaries, as an era best characterized as "early modern.""--
pt. 1. The context : social-historical factors in artistic production -- pt. 2. The artist : creative process and social status -- pt. 3. The object : art as material culture -- pt. 4. The message : subjects and meanings -- pt. 5. The viewer, the critic, and the historian : reception and interpretation as cultural discourse.
Includes bibliographical references and index.
Print version record.
Keywords: Art, Renaissance; Art, Baroque; ART -- History -- Renaissance; Art, Baroque; Art, Renaissance; Barock; Kunst; Renaissance; Electronic books